Cost Analysis of Antipsychotics Schizophrenia of Inpatients in Mental Hospital West Java Province: Analisis Biaya Antipsikotik Pasien Skizofrenia Rawat Inap di Rumah Sakit Jiwa Provinsi Jawa Barat - Indah Kurnia Utami; Melisa I. Barliana; Eli Halimah (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2022)
Schizophrenia is a mental disorder that can affect behavior, emotions and communication. In the agitation phase ithe patient is acompanied by destructive or violent behavior. In these conditions, the patient must immediately calm down to avoid risk. Monotherapy Treatment in acute agitation schizophrenia is recommended than combination therapy. The purpose of this study was to determine the effectiveness of treatment costs and the factors that influence the total cost of schizophrenia patients at the Mental Hospital of West Java Province. This study was observational by cross sectional study design according to the hospital perspective. This method is retrospective data. The subject were inpatients aged 18-65 years with diagnosis of schizophrenia disorder and receiving antipsychotic therapy for at least 1 month. The results showed that average cost-effectiveness ratio (ACER) Rp.288.659/ 1 score PANSS EC with an average decrease score of 9,70. There is a difference in variant data compared because p-value = 0.011<0,05. ICER calculation of A to C = (Rp. 2.800.001–Rp. 2.593.821) / (9.70 - 8.57) = Rp. 182.460. The factors that influence the total cost found that the most significant are administration and room. The conclusion is atypical-atypical monotherapy recommended as a treatment for schizophrenic in agitation acute.